Formação de capital social e o ideário do desenvolvimento sustentável no mundo rural rondoniense: a organização dos sistemas alternativos dos produtores de Ouro Preto D'Oeste - RO - MOSER, Lilian Maria (Universidade Federal do Pará, 2019)
The work aims to analyze the context and the performance of the Associação Alternativa de Produtores (Alternative Association of Producers - APA), organization founded in 1992 for a group of farmers of the municipal district of Ouro Preto of West, in the state of Rondônia, Brazil. With the purpose of supporting the projects of life its associated families and led from the ideal of the sustainable development APA stressed itself to overcome the crisis of the shifting cultivation among the migrating farmers, the ones which moved in the seventies and eighties by governmental politics in the Amazon Area, that implemented colonization projects and opened new moving frontiers by the construction of highways. The work reconstitutes the fundaments of the ideal of the sustainable development and the path of the development project that took those producers to Rondônia; it characterizes the institutional problems, beside the limits of technical nature with which they were confronted in the exercise of an agriculture of traditional feature; it reconstitutes also the motivations and movements that led to the foundation of the APA, verifying in what extension the values of civilism, solidarity and cooperation with perspectives of reaching the economic efficiency base the initiatives. Finally, analyze, starting from the results of primary research, if there is a correspondence among the ideals that forged the constitution of the Association and the reality its associates. In that moment it will be tested, comparing a group of associated with a group of not associated of APA, if its performance converges with the ideal of its foundation: if its politics is reflected in a larger economic efficiency, in a greater hope of sustainability of the productive systems managed by the families and, also, in a larger justness among them.